Nanoemulsion and Nanogel Containing Eucalyptus globulus Essential Oil; Larvicidal Activity and Antibacterial Properties - Alipanah, Hiva; Abdollahi, Abbas; Firooziyan, Samira; Zarenezhad, Elham; Jafari, Mojtaba; Osanloo, Mahmoud (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Eucalyptus globulus essential oil (EGEO) possesses many biological effects such as antibacterial, antifungal, and insecticide properties. In the current study, the chemical composition of EGEO was first investigated using GC-MS analysis. Then, a nanoemulsion and nanogel containing EGEO (EGEO-nanoemulsion and EGEO-nanogel) were prepared. After that, the successful loading of EGEO was confirmed using ATR-FTIR analysis. EGEO-nanoemulsion and EGEO-nanogel with LC50 values of 27 and 32 μg/mL showed promising efficacies against Anopheles stephensi larvae. Besides, the efficacy of EGEO-nanogel (IC50 187 μg/mL) was significantly more potent than EGEO-nanoemulsion (IC50 3732 μg/mL) against Staphylococcus aureus. However, no significant difference was observed in the efficacy of EGEO-nanoemulsion and EGEO-nanogel against Pseudomonas aeruginosa. Natural components, straightforward preparation, and proper efficacy are some of the advantages of EGEO-nanogel; it could be considered for further consideration against other pathogens and mosquito larvae.